Decision Support System For Recommending Expertise Programs Using Ahp Method - Setiawan, Alfin; Asnawati, Asnawati; Beti, Ila Yati (Jurnal Media Computer Science, 2025)
SMK Negeri 3 Kota Bengkulu is a Vocational High School located in Bengkulu Province. At SMK Negeri 3 Kota Bengkulu there are 5 (five) Expertise Programs that can be selected by new students including Culinary, Fashion, Beauty and Spa, Computer Network and Telecommunication Engineering (TJKT) and Broadcasting and Film. Every new student who wants to register must choose one of the expertise programs available at SMK Negeri 3 Bengkulu City. The decision support system in providing recommendations for expertise programs using AHP Method can help provide recommendations for expertise programs that are appropriate and in accordance with the assessment criteria for prospective new students and can be used as a forum to assist schools for recommending the expertise programs of prospective new students at SMK Negeri 3 Bengkulu City. A decision support system for recommending expertise programs using the AHP Method is built web-based applications that can be accessed offline. Based on system testing that has been carried out, it can be concluded that the functional of the decision support system application for recommending expertise programs using AHP Method has run well and has successfully carried out AHP Method process on prospective student value data according to the school year and provides information on the results of the expertise program recommendations for each prospective student.